Use of quali-quantitative feeding practices criteria in typology of smallholders’ dairy production systems - Dias,Angelica Petersen (2021)
ABSTRACT This study aimed to typify smallholders’ dairy systems using quali-quantitative measures of feeding practices and detect the main discriminatory elements identifying the systems. We collected data from 30 farms distributed in 10 municipalities in the eastern region of Rio Grande do Sul, Brazil, using a survey with semi-structured questions, in addition to bimonthly observations of milking and feeding practices. Multivariate analysis based on principal factors and cluster analysis were performed. Multiple linear regressions were made between the principal factors scores and variables of milk production and composition. Three principal factors with eigenvalues ≥1.0 explained 58.9% of the total variance. The original variables with the highest factor loading values were production scale and feeding practices involving greater quantities of byproducts; use of corn silage and sugarcane; and commercial and farm-made concentrate for principal factor 1, principal factor 2, and principal factor 3, respectively. Milk yield and concentrations of lactose and solids non-fat increased linearly with principal factor 1 and principal factor 3 but decreased linearly with principal factor 2. Observations were grouped into three clusters. Farm area and quantity of corn silage and byproducts were the most important variables to set the clusters. The use of quali-quantitative feeding practices criteria to characterize dairy systems is effective to identify the opportunities for improving milk production and composition. Whereas high inclusion of sugarcane as roughage was detrimental for milk production, moderate supply of concentrate and byproducts enhanced milk yield without compromising milk composition.